Antipsychotic Polypharmacy in Older Adult Asian Patients With Schizophrenia: Research on Asian Psychotropic Prescription Pattern. (November 2019) - Dong, Min; Zeng, Liang-Nan; Zhang, Qinge; Yang, Shu-Yu; Chen, Lian-Yu; Sim, Kang; He, Yan-Ling; Chiu, Helen Fung-Kum; Sartorius, Norman; Tan, Chay-Hoon; Chong, Mian-Yoon; Shinfuku, Naotaka; et al.
Background and Objective: Antipsychotic polypharmacy (APP) is a controversial topic in the treatment of older adults with schizophrenia. The objective of this study was to examine the use of APP in older adult Asian patients with schizophrenia and its associated demographic and clinical factors. Methods: This study was based on the fourth survey of the consortium known as the Research on Asian Psychotropic Prescription Pattern for Antipsychotics. Fifteen Asian countries/territories participated in this survey, including Bangladesh, Mainland China, Hong Kong, India, Indonesia, Japan, Korea, Malaysia, Myanmar, Pakistan, Singapore, Sri Lanka, Taiwan, Thailand, and Vietnam. Basic demographic and clinical characteristics were collected using a standardized data collection form. Results: Among the 879 older adults with schizophrenia included in the survey, the rate of APP was 40.5%. Multiple logistic regression analysis revealed that higher antipsychotic doses ( P < .001, odds ratio [OR] = 1.003, 95% confidence interval [CI]: 1.002-1.003), longer duration of illness ( P = .02, OR = 1.845, 95% CI: 1.087-3.132), and the prescription of anticholinergics ( P < .001, OR = 1.871, 95% CI: 1.329-2.635), second-generation antipsychotics ( P = .001, OR = 2.264, 95% CI: 1.453-3.529), and first-generation antipsychotics ( P < .001, OR = 3.344, 95% CI: 2.307-4.847) were significantly associated with APP. Conclusion: Antipsychotic polypharmacy was common in older adult Asian patients with schizophrenia. Compared to the results of previous surveys, the use of APP showed a declining trend over time. Considering the general poor health status of older patients with schizophrenia and their increased risk of drug-induced adverse events, the use of APP in this population needs careful consideration.